2012
DOI: 10.4172/2155-9619.1000122
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Perfusion Differences on Paired Tc-99m Macroaggregated Albumin (MAA) Hepatic Perfusion Imaging and Yttrium-90 (Y-90) Bremsstrahlung Imaging Studies in SIR-Sphere Radioembolization: Associations with Angiography

Abstract: Surgically unresectable primary and metastatic liver tumors have been increasingly treated with Y-90 radioembolization. In preparation for Y-90 radioembolization therapy, a baseline angiogram and a Tc-99m MAA hepatic perfusion study simulating Y-90 microsphere infusion are routinely performed, followed by a 2 nd angiogram in which the catheter is positioned in the same position as during the baseline angiography. However, radiotracer distribution on paired Tc-99m MAA hepatic perfusion imaging and post-therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 14 publications
2
45
0
2
Order By: Relevance
“…99m Tc-MAA scintigraphy may be considered a 'simulation study' for 90 Y resin microsphere predictive dosimetry" (supplemental data of (2)), yet he acknowledges in his letter that " 99m Tc-MAA is an imperfect surrogate for 90 Y microspheres." The latter assumption is well in line with the evidence from several other studies that investigated 99m Tc-MAA and 90 Y microsphere distribution in different tumor entities (3)(4)(5)(6). Consequently, relating 99m Tc-MAA distribution to the accumulated dose is a questionable practice.…”
supporting
confidence: 78%
“…99m Tc-MAA scintigraphy may be considered a 'simulation study' for 90 Y resin microsphere predictive dosimetry" (supplemental data of (2)), yet he acknowledges in his letter that " 99m Tc-MAA is an imperfect surrogate for 90 Y microspheres." The latter assumption is well in line with the evidence from several other studies that investigated 99m Tc-MAA and 90 Y microsphere distribution in different tumor entities (3)(4)(5)(6). Consequently, relating 99m Tc-MAA distribution to the accumulated dose is a questionable practice.…”
supporting
confidence: 78%
“…A study of RMS in 39 patients (with both HCC & metastatic lesions) segmented the liver into segments, and showed that for 68% of all segments (n=225), a difference of >10% between MAA and MS activity distribution was found, and that in every procedure at least 1 segment showed a >10% difference [58]. A similar study of 81 patients with a mix of HCC and metastases treated with RMS showed 31 patients had segmental perfusion differences, influenced highly by catheter position [75]. A recent study of 18 HCC patients treated with RMS found that the ratio of MAA to MS uptake in the tumour was 1.4:1, indicating that using MAA imaging for dosimetry calculations can overestimate D T [76].…”
Section: Using 99m Tc-maa As a 90 Y Ms Surrogatementioning
confidence: 88%
“…Surgical procedures have been identified as a cause of MAA-MS mismatch such as differences in injection rates, microcatheter positioning [75] and arterial flow hemodynamics [23]. A 5-10 mm difference in catheter position between tip and artery opening has been shown to have a major impact on microsphere flow distribution [58,77].…”
Section: Using 99m Tc-maa As a 90 Y Ms Surrogatementioning
confidence: 99%
“…The number of albumin particles is significantly lower than the number of injected 90 Y-microspheres (0.1-0.2 millions of MAA versus 30-60 millions of resin and 4-5 millions of glass particles), and a similar pattern is seen with the density (1.1 versus 1.6 g/mL for resin and 3.3 g/mL for glass particles). These features might explain why the mismatch problem seems to be more serious for embolic resin spheres [41][42][43]. The literature is controversial, however, since Kao et al [44], for instance, found excellent correspondence between 99m Tc-MAA SPECT and 90 Y PET dosimetry (median relative error 3.8 %).…”
Section: Treatment Planning With 99m Tc-maa Spectmentioning
confidence: 99%